ELECTRIC FIELD AND ITS ROLE IN LIFE - Khusniddinov Fakhriddin Shamsiddinovich,; Baratova Suhaylo Davronovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article provides an extensive and in-depth analysis of the theoretical foundations, historical development, modern scientific research, and the role of the electric field in life. It discusses fundamental concepts of the electric field, classical and modern theories, the contributions of regional and national scholars, empirical research findings, and practical applications. The article also addresses ongoing debates and issues, presenting scientifically grounded conclusions about the role of the electric field in various life processes.